Strategi Pricing dan Pengendalian Biaya pada UMKM di Fase Kedewasaan untuk Mempertahankan Profitabilitas - Yuni Estevania Siahaan; Emmanuella Theresia Oktaviana; Abdilah Abdilah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
MSMEs (Micro, Small, and Medium Enterprises) that are in the maturity phase face significant challenges in maintaining profitability due to competitive pressures, fluctuations in input costs, and changes in market demand. This study aims to analyze pricing strategies and the implementation of effective cost control in maintaining the profitability of MSMEs in this phase. The method used is a qualitative case study on several MSMEs that have achieved operational and revenue stability. The results show that a dynamic pricing approach—by adjusting prices based on market segmentation, product added value, and competitor analysis—plus cost control through process efficiency, inventory management, and supply chain optimization, is able to expand profit margins. This strategy also provides flexibility in adjusting the cost structure in the event of changes in the business environment, including raw material inflation or increased logistics costs. In addition, the use of digital technologies, such as accounting applications, cloud-based inventory management systems, and interactive financial dashboards, has been proven to increase transparency, accuracy, and data-driven decision-making. Human resource factors also play an important role in the successful implementation of cost control. Regular training, competency improvement, and performance-based incentives can reduce production errors and operational waste. Furthermore, collaboration with strategic partners, such as raw material providers and financing institutions, also helps to create efficiency and access to more competitive resources. In conclusion, the synergy between a responsive pricing strategy, digital transformation, and a disciplined cost control system is the key to sustainable profitability in MSMEs in the maturity phase. These findings are expected to be a practical reference for MSME actors in developing financial policies and operational strategies that are adaptive to market dynamics and business competition.